Awareness and Competence of Pediatricians on Child Abuse: Preliminary Results of the International Cross-Sectional Study - Leyla S. Namazova-Baranova; Natalia V. Ustinova; Valeriy Yu. Albitcky; Kamilla E. Efendiyeva; Stella E. Sher; Elena A. Vishneva; Andrey V. Shulaev; Marat M. Sadykov; Airat I. Ziatdinov; Rafael F. Shavaliev (Педиатрическая фармакология, 2020)
Background. Many social problems have worsened nowadays especially in the context of the COVID-19 pandemic. It is important that child health professionals have all the necessary knowledge for detection of child abuse in modern society. Aim of the study is to study the awareness and competence of pediatricians on child abuse. Methods. The cross-sectional study was conducted using the international standardized questionnaire (22 questions). The study has included practicing pediatricians from inpatient and outpatient (95% of all respondents) clinics in Kazan. Results. The data from questionnaire survey of 73 pediatricians has shown that 29 (40%) and 39 (53%) of all respondents encountered physical and psychological abuse against children, respectively. Physical abuse was considered as the most common form of abuse by 38 (52%) pediatricians. The child abuse was revealed during routine examination in 33 (45%) cases. 20 (28%) respondents have initiated proceedings for every case of physical abuse, and 23 (31%) — for psychological abuse. One in three pediatricians, 23 (31%), consider the present legislation comprehensive enough in the sphere of children protection against abuse. Meanwhile, 50 (68%) pediatricians regarded their own level of awareness in this topic as insufficient. Conclusion. The study has shown insufficient competence of pediatricians (especially in the visiting services) in the detection and maintenance of children abuse cases (physical and psychological). It is crucial to enhance and continuously improve education of pediatricians on pre-graduate and continuing professional education levels in issues of children abuse.